Por mais terras que eu percorra: relatos testemunhais de ex-comandantes da FEB - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This Course Conclusion Work sought to work with Memorialist Literature, through the reports and testimonies of ex-fighters of the Brazilian Expeditionary Force (FEB). The objective for the study was to bring to knowledge the reports of war experience and an autobiographical narrative of the expeditionaries in the 2nd World War (1939 - 1945), inserting them in the study of Memorialist Literature. The methodology used was bibliographic research, collecting data and consulting authors in the areas of History of the 2nd World War, Brazilian participation in the event and Memorialist Literature, with an emphasis on veterans' testimonies and an autobiography. To complement the studies, theorists on Memorialist and Testimony Literature were used, with emphasis on Alba Olmi. Finally, these reports and testimonies are respectively present in the two works “Vozes da Guerra” by Sirio Sebastião Fröhlich (2015) and Boris Schnaiderman (2015) with “Caderno Italiano”. Both were released in the same year, but with relevant points of view, in the “how to tell the story” mode. In “Vozes da Guerra” the author rescued the memories through interviews with the veterans who participated in the armed clash; the work of Boris Schaiderman (2015), written when the author was already old, is an autobiographical account of his participation in the FEB as a young man. About what can be considered from the study of the reports, over time, we seek to honor and rescue the memory of these brave people who made a difference and today are evoked with honor, so that future generations can access and seek to understand how those young people left their homes and went to fight not only against a powerful army, but against all the adversities that were imposed on them. Memorialist Literature can help to understand how these historical facts are present in testimonial reports, making Literature and History walk together.
Keywords: 2ª Guerra Mundial; Força Expedicionária Brasileira; Literatura Memorialista; 2nd World War; Brazilian Expeditionary Force; Memorialist Literature; CNPQ::LINGUISTICA, LETRAS E ARTES